Revisión sobre la definición de Psicología Jurídica (2010)
In the following article, a result of the reflection born within the project grade for the Master in Legal Psychology, will present a review on definitions and the terms used to designate a new area of psychology, called by many Juridical Psychology. Three issues are concluded, on the one hand, there are many words used incorrectly as synonyms, on the other there is no consensus against what psychologists mean by Legal Psychology, and finally that most existing definitions do not contain the rules you must see a definition in a scientific context. These situations cause effects on the epistemological assumptions that guide and on the limits of this area compared to other areas and disciplines.